Caracterização citogenética e morfométrica em populações de Leptodactylus fuscus Schneider, 1799 e Leptodactylus latrans Steffen, 1815 (Anura,Leptodactylidae) em áreas de caatinga do estado de Sergipe - Oliveira, Betejane de (2011)
The genus Leptodactylus has wide distribution and it can be found in many physiographic and climatic zones. This fact has raised questions about the taxonomy of this genus because many species that are considered of great geographic distribution has shown to be two or more closely related. The species Leptodactylus fuscus and Leptodactylus latrans, both widely spread, are found in the state of Sergipe in the Caatinga biome and little is known about the ecology, biology and diversity between and within populations that occupy this exclusively Brazilian biome. Therefore, the present study aimed to characterize the species L. fuscus and L. latrans, which occur in different fragments of Caatinga from the state of Sergipe, using cytogenetic and morphometric data. The karyotypes of populations from the municipalities of Carira, Poço Redondo and Tobias Barreto were analyzed by conventional staining techniques, C-band and Ag-RON. The species showed similar cytogenetic patterns, without evidence of species-specific markers; however some variations in morphology and bands were observed when compared to the karyotypes described in the literature. In morphometric analysis, 21 different characters were analyzed in the two species in each location, showing that populations of L. fuscus presented no significant differences between them; however variations were found in samples of L. latrans, mainly on the size of the specimens. The analyzed data showed that there were no cytogenetic and morphometric differences within the L. fuscus populations and that the morphometric variations observed in L. latrans may be due to environmental effects.